Bad hair days in the paleolithic : modern (Re) constructions of the cave man. - Berman, Judith C. (American Antropological Association, 1999)
Although we have never seen Paleolithic humans in the flesh, we recognize them immediately in illustrations, art, cartoons, and museum displays. The familiar iconography of the "Cave Man" often depicts our early human ancestors with longish, unkempt hair. However, this conventionalized image is not congruent with available archaeological data on the appearance of Upper Paleolithic humans. The lengthy iconographic history of representations of our prehistoric humans is rather a palimpsest of beliefs about the origins of humans, "natural man," human nature, primitive humans, and the savage "Other": a history of discourses about human evolution, human language, and the place of humans in the natural world. These images are traced in their anthropological, evolutionary, and philosophical contexts from medieval art through recent scientific illustrations, art, cartoons, and murals, and their influence on the scientific interpretation of our ancestors is assessed.